IMPLEMENTASI SAK EMKM UNTUK PENINGKATAN LABA USAHA UMKM - Haliza, Sabrina Ainur; Muzakki, Kafidin (JURNAL AKUNTANSI BARELANG, 2025)
The purpose of this study was to determine the Implementation of Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) in preparing financial reports on Broiler Duck Farming MSMEs in order to help MSMEs in increasing business profits. This research uses a qualitative method with a descriptive approach, with data collection techniques including observation, documentation, literature and interviews with MSME owners. The results showed that butcher Duck MSMEs have implemented recording financial statements based on SAK EMKM, the reports prepared include profit and loss statements, statements of financial position and also notes to financial statements (CALK). With the application of SAK EMKM, business profits have increased from May to June 2024. The previous revenue of Rp 8,600,000 increased to Rp 10,200,000 while the operating profit increased from Rp 3,025,000 to Rp 4,530,000. This shows the successful implementation of improved financial management according to SAK EMKM, which is driven by more effective management of cost of goods sold and optimization of operational costs.